2017
DOI: 10.1159/000456667
|View full text |Cite
|
Sign up to set email alerts
|

Readmissions and Emergency Department Visits after Bariatric Surgery at Saudi Arabian Hospital: The Rates, Reasons, and Risk Factors

Abstract: Background: Saudi Arabian hospital readmissions and emergency department (ED) visits following bariatric surgery and discharge have never been investigated. This study aimed to evaluate the rates and reasons of hospital readmissions and ED visits related to surgical weight loss interventions at the King Abdulaziz Medical City - Riyadh. Methods: We conducted a retrospective cohort study on 301 patients who underwent bariatric surgery between January 2011 and July 2016. We reviewed patient medical records progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 41 publications
2
21
3
1
Order By: Relevance
“…Recently, Ahmed et al, in a study conducted at King Abdulaziz Medical City in Riyadh, reported a hospital readmission rate of 8% and an emergency department visit rate of 14% in obese Saudi patients who underwent bariatric surgery. 25 According to this study, LSG was associated with fewer hospital readmissions or emergency department visits as compared to RYGB.…”
Section: Introductionmentioning
confidence: 62%
“…Recently, Ahmed et al, in a study conducted at King Abdulaziz Medical City in Riyadh, reported a hospital readmission rate of 8% and an emergency department visit rate of 14% in obese Saudi patients who underwent bariatric surgery. 25 According to this study, LSG was associated with fewer hospital readmissions or emergency department visits as compared to RYGB.…”
Section: Introductionmentioning
confidence: 62%
“…The ED revisit within 72 hours has been widely reported in earlier studies, and its rate depends on the chronic disease status and the cultural background. 6 12 The rates of 72-hour ED revisits may depend on age, 10 , 11 gender, 10 , 13 disease categories, 6 – 8 , 12 medical errors, 7 , 8 patients, 7 and doctors. 7 Although data regarding ED revisits within 72 hours can be used to implement changes and modifications to improve the electronic medical record database, the rate of revisits to the ED within 72 hours has not been documented among adults with chronic diseases in Saudi Arabia, particularly in our center.…”
Section: Introductionmentioning
confidence: 99%
“…[15], medical (nutritional deficiencies, kidney stones, bone fragility, hyperinsulinemic hypoglycemia, etc) [16] and psychiatric (self-harm, substance abuse) [17]. The likelihood of consultations to emergency departments and accumulation of diagnostic irradiation by computer tomography might be also elevated after BS [18]. RYGB has the additional sequel of making the choledochus inaccessible orally, complicating the eventual future treatment of bile duct lithiasis, which is why some surgeons advocate concomitant prophylactic cholecystectomy [19].…”
Section: Knowledge On Benefits and Risks Of Bariatric Surgerymentioning
confidence: 99%